Conjugated Linoleic Acid and other Fatty Acid Content in the Milk Fat of Mafriwal and Jersey Cows and the Antioxidant Activity of Selected Conjugated Linoleic Acids Isomers - Mohammed Ali, Yassir (2010)
Special attention has been given to the milk fatty acids (FA) such mono and poly unsaturated fatty acids particularly the conjugated linoleic acids (CLA) that have beneficial effects for human health. The present study was undertaken to investigate the breed effect on CLA and other fatty acid contents in cow milk fat and to assess the antioxidant activity of cis-9, trans-11 and trans-10, cis-12 as a single or mixed CLA isomers. Milk samples were obtained from 30 lactating cows from two breeds, Marfiwal (n=15) and Jersey (n=15) from Institut Haiwan Kluang, Johor, Malaysia. All the cows were grazed on pasture and given 5.5 kg of concentrate per head daily. Milk fatty acid content was determined using standard gas chromatography. The mean value of cis-9, trans-11 CLA in milk fat of Mafriwal (3.5 mg/g of total fatty acids) was significantly higher (P < 0.05) than that of Jersey cows (2.3 mg/g of total fatty acids). The mean values of trans-10, cis-12 CLA were 0.3 and 0.25 mg/g of total fatty acids for Mafriwal and Jersey cows, respectively, which were not significantly different (P > 0.05). however, the CLA-desaturase index was significantly (P < 0.05) higher in Mafriwal than that of Jersey cows. A significantly positive correlation (r = 0.423, P < 0.05) was observed between cis-9, trans-11 CLA and milk production. The CLA-desaturase index was also positively correlated (r = 0.636, P < 0.010 with milk production. As for the antioxidant activity, a microplate reader was used to determine the free radical scavenging properties of trans-10, cis-12 and cis-9, trans-11 as single or mixed at two ratios, 1:6 and 1:13 (trans-10, cis-12/ cis-9, trans-11), against the stable 2, 2-diphenyl-1- picryhydrazyl radical (DPPH) in ethanol. The kinetic reactions of CLA-DPPH˙ showed that trans-10, cis-12 and cis-9, trans-11 as single or mixed CLA isomers have exerted radical scavenging activities in a dose-dependent manner with the lowest concentration of 2.5 mg of CLA/mL in ethanol. The two CLA isomers and the mixtures were observed to immediately react and quench DPPH radicals at all tested levels and no lag phase was noticed in CLA-DPPH˙ reactions. The median inhibitory concentration (IC 50) value for cis-9m trabs-11 CLA (11.1 ±3.8 mg/mL) was observed to be more effective than trans-10, cis-12 CLA (12.6 ±3.4 mg/mL) and the mixtures of trans-10, cis-9, trans-11 at the ratios of 1:6 and 1:13 (16.3 ±1.1 mg/mL and 27.9 ±8 ng/mL), respectively. Furthermore, cis-9, trans-11 CLA quenched significantly more (P < 0.05) DPPH radicals at low concentrations (5 and 10 mg/mL) than that of trans-10, cis-12 CLA and the two mixtures f trans-10, cis-12 and cis9, trans-11 at the ratios of 1:6 and 1:13 (trans-10, cis-12/ cis -9, trans-11). Meanwhile, trans-10, cis-12 CLA quenched significantly more (P < 0.05) DPPH radicals at high concentrations (40 and 80mg/ml) than the other tested CLAs. Total antioxidant capacity (TAC) of CLA as single or mixed isomers was estimated and compared with the potent antioxidants such as vitamin E (vit E) and butylated hydroxytoluene (BHT). All tested CLAs were less effective radical scavengers as compared to bit E and BHT at a level of 50 mM, although all tested CLAs quenched a high amount (P < 0.05) of DPPH free radicals. Conversely, TAC if trans-10, cis-12 CLA was significantly more (P < 0.05) effective than the other tested CLAs followed by cis-9, trans-11 CLA, the mixture of trans-10, cis-12 and cis-9, trans-11 at ratio of 1:6 and the mixture of trans-10, cis-12 and cis-9, trans-11 at ratio of 1:13. In conclution, the breed factor has a considerable effect on CKLA concentration and other FA content in cows’ milk fat. The Mafriwal cows had significantly (P < 0.05) higher concentrations of CLA in their milk fat than that of the Jersey cows, which would provide a better benefit to human health. In addition, the CLAs had the ability to directly react and quench DPPH free radicals in ethanol, suggesting that the free radical scavenging activity of the CLA isomers may contribute to their diverse biological activities.